2023
DOI: 10.1002/alz.063408
|View full text |Cite
|
Sign up to set email alerts
|

The association between Alzheimer’s disease blood‐based biomarkers and cognitive impairment and probable dementia in Look AHEAD MIND

Abstract: Background:The effect of an intensive lifestyle intervention (ILI) on Alzheimer's disease (AD) blood-based biomarker levels and cognitive outcomes among individuals with type 2 diabetes (T2D) is unknown. We examined AD biomarkers and cognitive outcomes in the Look AHEAD Study. Method: Participants aged 45-76 years were randomized at baseline to a 10-year ILI or a diabetes support and education (DSE) condition. Cognitive assessments at years 8-18 included measures of attention, executive function, global functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
4
0
0
Order By: Relevance
“…NfL also significantly increased between adolescence and young adulthood in the Y-DM group. Again, these results are consistent with other, larger studies in adults with diabetes, where serum and plasma NfL are shown to be significantly higher, compared to nondiabetic reference groups, and increase with greater diabetes duration [45,49]. Despite this consistency, we exercise caution with the interpretation of our NfL results, given that NfL is a non-specific marker of neuron damage and could also indicate involvement from peripheral neuropathy in people with diabetes [50,51].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…NfL also significantly increased between adolescence and young adulthood in the Y-DM group. Again, these results are consistent with other, larger studies in adults with diabetes, where serum and plasma NfL are shown to be significantly higher, compared to nondiabetic reference groups, and increase with greater diabetes duration [45,49]. Despite this consistency, we exercise caution with the interpretation of our NfL results, given that NfL is a non-specific marker of neuron damage and could also indicate involvement from peripheral neuropathy in people with diabetes [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in this same study, serum GFAP levels followed a dose-response relationship where GFAP increased from cognitively unimpaired without T2D, to T2D only, to cognitively impaired only, and finally to T2D with cognitive impairment, suggesting that the presence of T2D confers added neuroimmune stress above and beyond that which underlies general cognitive impairment. Among our Y-DM group, the significant increase in plasma GFAP levels over the approximately 12-year follow-up period is also consistent with the Look AHEAD study, where they too observed significantly increased plasma GFAP levels in adults with T2D over an 8-to-13-year follow-up period [45].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations